PERAN STRATEGI 4P DALAM MENINGKATKAN BRAND AWARENESS DAN LOYALITAS PELANGGAN DI ERA DIGITAL - Rahmayanti, Vera; Nurhikmah, Nurhikmah; Fitri, Nur Aulia; Sabbar, Sabbar Dahham; Farida, Ida (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
The present journal aims to describe the role of marketing strategies, namely the marketing mix (also known as 4P: Product, Price, Promotion, Place) in increasing brand awareness and customer loyalty, especially in the growing digital era. This research is a library research study, namely by collecting and analyzing various written data from relevant sources. The digital revolution has profoundly altered the way we live, ushering in novel opportunities and challenges that have never before been experienced, including in the business paradigm, as evidenced by the intensifying competition between companies. These changes necessitate that companies perpetually innovate and update their marketing strategies. The 4P strategy (product, price, place, promotion) plays a pivotal role in increasing brand awareness and customer loyalty in the digital era. In the contemporary business landscape, enterprises are compelled to adopt an innovative approach to their online products, pricing strategies, distribution networks, and promotional initiatives to achieve a broader market reach. By leveraging digital technologies, companies can cultivate deeper customer relationships, enhance brand visibility, and personalize experiences, thereby fortifying customer loyalty and ensuring long-term success. However, this endeavor is not without its challenges, as enterprises must navigate a landscape characterized by diverse consumer preferences, rapid technological advancements, and intense competition. Consequently, companies must embrace continuous innovation and adaptation of marketing strategies to maintain relevance in the continually evolving digital market.